Contribution Fiscal Policy to Economic Growth in East Java - Muhammad Farhan Mochtar; Sishadiyati , Sishadiyati (Publikasi Inspirasi Indonesia, 2025)
This study empirically examines the impact of fiscal policy on economic growth in East Java Province during the period 2018–2024. The objective is to analyze the effects of regional taxes, subsidy expenditures, and the Value Added Tax (VAT) rate adjustment on regional economic growth. A quantitative approach with multiple linear regression analysis is employed, incorporating a dummy variable to capture the impact of the VAT increase from 10% to 11% in 2022. The findings reveal that regional taxes and the VAT dummy variable significantly influence economic growth, while subsidy expenditures are statistically insignificant. The coefficient of determination (R²) of 96.5% indicates that the model explains the majority of variations in economic growth. These results imply that optimizing tax revenues and evaluating VAT policy should be aligned with strategies for inclusive and sustainable regional economic growth. This research provides relevant insights for regional policymakers in designing effective fiscal instruments.